COVID-19 pandemic through the lens of rights of persons with disabilities and state responsibilities in social protection and labour market - Jovanovska, Bojana; Petkovska, Natasha (Ревија за социјална политика/Journal of Social Policy, 2012)
The crisis caused by the coronavirus pandemic managed to intensify and in a very short time it brought to the surface the problems the marginalized citizens faced with in the society, which include people with disabilities, as well as their caregivers. Taking into consideration the continuing marginalization of people with disabilities in North Macedonia, with the support of the Westminster Foundation for Democracy, the authors of this paper conducted a brief survey on the Impact of the Covid-19 Crisis on People with Disabilities in North Macedonia, published in May, 2021. The survey covered a period of one year, i.e., from the beginning of the pandemic with the declaration of the state of emergency. This paper is based on the conducted survey, and the aim is to present the situation that people with disabilities and their caregivers experienced as a result of the measures and policies that were adopted during the pandemic, and resulting from the pandemic itself, with a special focus on the situation in the field of social protection and the labour market. The challenges faced by people with disabilities that existed long before the pandemic, such as increasingly present stereotypes and prejudices, inaccessible infrastructure, discriminatory practices in the education system and the labour market, but also non-accountable institutions, were significantly emphasized as a result of the inadequate coping with the pandemic caused by Covid-19. This only confirmed the unfavourable position of people with disabilities, but also of their caregivers, in terms of opportunities to ensure a quality life. The challenges faced by people with disabilities in terms of access to social protection and their inclusion in the labour market were particularly difficult, considering that the restrictive measures for prevention and protection from Covid-19 were not in line with the needs, i.e., the possibilities of people with disabilities.